2018
DOI: 10.1002/ca.23254
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of smooth muscle tissue in the male pelvic floor with special reference to the lateral extent of the rectourethralis muscle: Application to prostatectomy and proctectomy

Abstract: The anatomy of the rectourethralis muscle is essential for performing radical prostatectomy and proctectomy. The rectourethralis muscle is known to continue to the rectal wall posteriorly and to the membranous urethra anteriorly. However, the lateral extent of the rectourethralis muscle remains unclear. This study aimed to verify the hypothesis that the rectourethralis muscle laterally extends and directly adheres to the levator ani. Eight male cadavers were used for macroscopic dissection, and three male cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 37 publications
(55 reference statements)
4
62
0
Order By: Relevance
“…The anterior extension of the smooth muscle of the anorectal canal has been confirmed in males. The smooth muscle structure anteriorly, extending to the posterior urethra, is termed the rectourethralis muscle, whereas the smooth muscle structure extending antero‐inferiorly to cover the anterior surface of the external anal sphincter was reported as the anterior bundle of the longitudinal muscle . The anterior extension structure of the internal anal sphincter and rectal longitudinal muscle described in our study (indicated by the star in Figs b, c and d, h) is considered to be the structure homologous to the rectourethralis muscle of males, on the basis of the location, morphology and tissue composition.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The anterior extension of the smooth muscle of the anorectal canal has been confirmed in males. The smooth muscle structure anteriorly, extending to the posterior urethra, is termed the rectourethralis muscle, whereas the smooth muscle structure extending antero‐inferiorly to cover the anterior surface of the external anal sphincter was reported as the anterior bundle of the longitudinal muscle . The anterior extension structure of the internal anal sphincter and rectal longitudinal muscle described in our study (indicated by the star in Figs b, c and d, h) is considered to be the structure homologous to the rectourethralis muscle of males, on the basis of the location, morphology and tissue composition.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, researchers who clarified the anatomical planes for an extralevator abdominoperineal excision have for a long time realized that the interface between the anterior anorectal wall and the structures of the posterior genitourinary complex have many similarities in males and females, including a fibromuscular point (perineal body) that serves as a connecting point in the middle of the non‐bony pelvis . The perineal body refers to the fibromuscular tissue in the region between the rectum and urogenital structures . Larson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only smooth muscles allow that degree of stretching without injury (Seow and Solway, ). Accordingly, several studies have confirmed its status as a smooth muscle (Nakajima et al, ; Muro et al, , ). The developmental anatomy of the rectourethral muscle and perineal body can account for much of the controversies that surround the deep perineal muscle (Table ).…”
Section: New Findingsmentioning
confidence: 90%
“…Although the perineal body is an acknowledged item in “Anatomical Terminology” (A09.5.00.0005 (Terminol, )), it is not universally accepted as a specific structure. Thus, Akita and colleagues argue that description of the perineal body as a node is a too delimited description and should, instead, be considered a region (Muro et al, ). However, our description of the perineal body as a fibromuscular structure in the wedge‐shaped space between the lower portion of the rectum and the vagina or urethra (“region”) that penetrates with many antenna‐like extensions between the fibers of the rectourethral muscle (“shape”) (Wu et al, ; Wu et al, ; Wu et al, ) is not very different from the impression that emanates from their trichrome‐stained illustrations of the rectourethral muscle (Muro et al, ).…”
Section: New Findingsmentioning
confidence: 99%